THE TAX CULTURE OF SOCIETY: THE CRITERIA OF ASSESS AND CHARACTERISTICS OF THE CURRENT CONDITION - Vladimir Kuzmenko; Dmitry Bondarev (Вестник Северо-Кавказского федерального университета)
This is scientific article involves criteria that were considered and suggested for practical application. These criteria assist to assess the level of tax culture in society. There are results theoretical and practical researches for the level of tax culture influence on the forming budget revenues processes in the scientific article. The criteria for assessing the level of tax culture influence on the forming budget revenues processes are proposed. Also, were suggested the mechanisms of state regulation and the activities of tax authorities aimed at raising the level of tax culture in the society and ways for improvement all of it. The level of interrelation between the deficit of budgets of all levels and the general level of tax culture is considered too. In addition, were determined the economic and social factors that negatively effect on the level of tax culture